Bracing the athlete`s back: Efficacy and indications - McNair, P. J. (International SportMed Journal, 2000)
To date, research into the effects of back belts has been focused upon lifting tasks rather than their use in athletes. It has been shown that back belts can decrease range of motion and increase the stiffness of the trunk, though these changes may be confined to specific planes of motion. There is incomplete evidence to conclude that a certain type of belt is most beneficial for a particular activity. It is apparent that the effect of back belts on strength, endurance, and fatigue is very limited. At this time, there is a need for epidemiological studies examining the effects of belts on injury rates in both sporting and industrial settings.